Fatty Acid Profile of Hepatopancreas and Oocyte of Tiger Shrimp, Penaeus monodon, Fed Modified-commercial Diet by Supplementing Vitamin C and E - Usman, Usman; Kamaruddin, Kamaruddin; Laining, Asda; Trismawanti, Ike (Indonesian Aquaculture Society (MAI), 2019)
Vitamin C and E have important roles in the process of reproduction, immune system, and anti-oxidants to protect cell membrane lipid, and the circulation of essential fatty acid in the body of the aquatic organism including shrimp. The aims of this study was to analyze the effect of vitamin C and E supplementation in modified-commercial diet on the fatty acids profile of hepatopancreas and oocyte of tiger shrimp, Penaeus monodon. The experimental treatments were: modified-commercial diet by supplementing with vitamin C (500 mg/kg) and E (300 mg/kg) (PS), and modified-commercial diet without vitamins supplementation (PK). Cultured tiger shrimp were used as the animal with initial weight of 43.1 ± 5.1 g (mean±STD) for females and 41.9 ± 4.4 g for males. The shrimps were cultured in two of 1000 m2 concrete ponds with a density of 100 shrimp / pond. During three months culture in the pond, they were fed the test at rate of 3% biomass/day. When the tiger shrimp reached the weight over 90 g for females and > 70 g for males, then the shrimp were transferred to concrete tanks for oocyte maturation evaluation. In maturation tank, the shrimp fed test diets (pellet) combined with fresh food (squid) as much as 3% (dry basis) at combination ratio of 50% : 50%. Shrimp reaching oocyte development stage III were dissected and sampled for hepatopancreas and oocytes for analysis of fatty acid profile. The results showed that the hepatopancrea and oocyte fatty acids contents were higher in the tiger shrimp fed PS compared to the tiger shrimp fed PK. The poly unsaturated fatty acid (PUFA) especially for arachidonic, docosahexaenoic, and eicosapentaenoic acid were higher in shrimp fed with PS than the shrimp fed PK. Despite higher total fatty acid contents in hepatopancreas than in oocyte for the both treatments, the esensial fatty acid arachidonic, docosahexaenoic, and eicosapentaenoic acid were higher in oocyte than in hepatopancreas of the shrimp. This suggested that these three types of PUFA played important role for oocyte development for female reproduction. Supplementation of vitamin C and E in the test diet had an effect on increasing PUFA content in hepatopancreas and oocytes of tiger shrimp.